(untitled) - Shaw, Elizabeth M. (London, 1998)
The book is essentially practical, emphasizing the application of hydrological knowledge to the solution of engineering problems. The book culminates in a selection of civil engineering spheres of operation requiring hydrological expertise, demonstrating some of the established methods and some of the new techniques applied in current practice
Keywords: Water supply engineering